2010
DOI: 10.1088/0022-3727/43/30/302001
|View full text |Cite
|
Sign up to set email alerts
|

Emission wavelength extension of mid-infrared InAsSb/InP nanostructures using InGaAsSb sandwich layers

Abstract: This paper presents a study on the emission wavelength extension of InAsSb nanostructures using InGaAsSb sandwich layers. Due to the reduced lattice mismatch between InAsSb nanostructure layer and buffer/capping layer, the introduction of InGaAsSb sandwich layers leads to larger island size, reduced compressive strain and lower confinement barrier for InAsSb nanostructures, thus resulting in a longer emission wavelength. For InGaAsSb sandwich layers with nominal Sb concentration higher than 10%, type II band a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…These nanostructures have potential applications in mid-infrared optoelectronic devices. [8][9][10][11][12] It is found that by using different graded approaches the actual Sb composition in InAsSb nanostructures can be changed significantly despite the fact that their nominal Sb mole fraction (averaged over the graded growth) is kept the same, which results in different morphologies for the InAsSb nanostructures. As a result of their composition and morphological changes, photoluminescence from these InAsSb nanostructures shows different polarization and temperature characteristics.…”
mentioning
confidence: 99%
“…These nanostructures have potential applications in mid-infrared optoelectronic devices. [8][9][10][11][12] It is found that by using different graded approaches the actual Sb composition in InAsSb nanostructures can be changed significantly despite the fact that their nominal Sb mole fraction (averaged over the graded growth) is kept the same, which results in different morphologies for the InAsSb nanostructures. As a result of their composition and morphological changes, photoluminescence from these InAsSb nanostructures shows different polarization and temperature characteristics.…”
mentioning
confidence: 99%
“…[1][2][3][4][5] Some work has been devoted to the direct growth of InAsSb nanostructures by Stranski-Krastonow method, and flat InAsSb quantum dots ͑QDs͒ with high density can be achieved by using InGaAs buffer layer and proper growth parameters. 9 Unfortunately, the emission efficiency of these InAsSb/InP nanostructures is much lower than that of InAs/InP QDs, especially at high temperatures. 9 Unfortunately, the emission efficiency of these InAsSb/InP nanostructures is much lower than that of InAs/InP QDs, especially at high temperatures.…”
mentioning
confidence: 99%